Answer:
m<T = , m<M = and m<Z =
Step-by-step explanation:
From the given ∆TMZ, let the measure angle T be represented by T.
So that,
m<M = 2T + 6°
m<Z = 5T - 50°
Sum of angles in a triangle =
T + (2T + 6°) + (5T - 50°) =
8T - =
8T = +
=
T =
=
Therefore,
i. m<T =
ii. m<M = 2T + 6°
= 2 x + 6°
=
m<M =
iii. m<Z = 5T - 50°
= 5 x - 50°
= - 50°
=
m<Z =
Answer:
All answers in this set can be written in the form y=f(x).
The answer should be t=-24
Easy! Just substitute.
That will be 3 + 8 * 4
Remember PEMDAS? Multiplication comes before addition, so FIRT MULTIPLY.
3+ 32= 35
Final answer= 35
The "e" is one of mathematical constants. It's equal to approximately 2.7. It's sometimes called Euler's number.<span />